2014
DOI: 10.1242/jeb.103705
|View full text |Cite
|
Sign up to set email alerts
|

Limits to sustained energy intake. XXII. Reproductive performance of two selected mouse lines with different thermal conductance

Abstract: Maximal sustained energy intake (SusEI) appears limited, but the factors imposing the limit are disputed. We studied reproductive performance in two lines of mice selected for high and low food intake (MH and ML, respectively), and known to have large differences in thermal conductance (29% higher in the MH line at 21°C). When these mice raised their natural litters, their metabolisable energy intake significantly increased over the first 13 days of lactation and then reached a plateau. At peak lactation, MH m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 82 publications
(115 reference statements)
2
4
0
Order By: Relevance
“…As in previous studies, there were no differences in BM between mice from the L and H strain prior to mating, but reproductive success was increased in mice of the H line24. That is mice from the H line produced larger litters and weaned larger pups.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…As in previous studies, there were no differences in BM between mice from the L and H strain prior to mating, but reproductive success was increased in mice of the H line24. That is mice from the H line produced larger litters and weaned larger pups.…”
Section: Discussionsupporting
confidence: 71%
“…We measured a variety of biomarkers of oxidative stress, and compared these in lactating (R) and non-reproducing mice from two strains that had been selected for different levels of FI, that we have previously shown differ significantly in their levels of reproductive performance24.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous comparison of two mouse strains selected for different levels of thermal conductance found that the strain with lower thermal conductance assimilated less energy, produced less milk and had lighter litters at weaning than the strain with higher thermal conductance (Al Jothery et al, 2014). The results of our temperature experiment support the HDL hypothesis, which suggests that animals subject to warmer ambient temperatures have to restrict the production of body heat associated with food input and energy expenditure Król, 2005, 2011).…”
Section: The Effects Of Litter Size On Energy Balancesupporting
confidence: 77%